DEVELOPMENT OF SYMMETRICAL AND ASYMMETRICAL FABRICS IN SHEET-LIKE IGNEOUS BODIES: THE ROLE OF MAGMA FLOW AND WALL-ROCK DISPLACEMENTS IN THEORETICAL AND NATURAL CASES - Correa-Gomes L.C.; Souza Filho C.R.; Martins C.J.F.N.; Oliveira E.P. (My University, 2001)
Two orientations of fabrics are recognised in vertical dykes: a symmetric orientation associated with magma injected into non-deforming wall-rocks and an asymmetric orientation usually associated with external non-coaxial shearing, or magma injected into an active fault. The notion of two fabric arrangements stems from two planes of symmetry, the dyke symmetry plane (DSP) and the fabric symmetry plane (FSP). This paper uses conceptual models to simulate all possible orientations of magma flow indicators that might be produced within a vertical dyke emplaced under coeval internal and external stresses. The effect of magmatic buoyancy-related stresses are portrayed in terms of magma flow velocities (MFV) and the external non-coaxial tectonic-related stresses in terms of wall displacement velocities divided by two (WMV/2). The tectonic setting is that of a sinistral transcurrent fault.Using these assumptions, five cases are proposed: MFV#WDV/2, MFV>WDV/2, MFV=WDV/2, MFV